Exploring Adolescent Reproductive Health Education Needs for Digital Application Development: A Qualitative Needs Assessment - Eti Salafas; Haryono; Irwan Budiono; Evi Widowati (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Adolescent reproductive health (ARH) education is an effort to improve health literacy and support healthy behaviours. However, many adolescents still experience limited access to credible information on reproductive health due to inadequate school-based education, sociocultural stigma, and barriers to open communication. Although digital education approaches are increasingly promoted, evidence regarding adolescents’ educational needs and stakeholder perspectives to inform contextually relevant digital interventions remains limited. This study aims to explore adolescent reproductive health education needs and identify considerations for the future development of a digital educational application. Methods: A qualitative needs assessment design was employed. Data were collected between September and November 2025 through semi-structured interviews and focus group discussions involving junior high school students (n = 6), teachers (n = 3), and health and government stakeholders (n = 8), who were purposively selected. All interviews and discussions were audio-recorded, transcribed verbatim, and analysed using Braun and Clarke’s six-phase thematic analysis framework, with NVivo 15 used to support data management and coding. Results: Six major themes were identified: reproductive health literacy gaps, adolescent behavioural risks, barriers in school-based reproductive health education, limitations in teacher capacity and learning resources, challenges in policy and programme implementation, and the need for innovative digital reproductive health education applications. These findings revealed a mismatch between adolescents’ preference for private, practical, and digitally accessible reproductive health information and the limited readiness of schools, teachers, families, and existing support systems to provide structured, credible, and non-stigmatising education. Participants emphasised the need for age-appropriate content, confidential access to information, interactive learning features, stronger teacher support, and better integration with existing school and health programmes. Conclusion: This study provides formative empirical evidence regarding adolescent reproductive health education needs and preliminary requirements for digital application design. The findings may inform the development of adolescent-centred educational technologies and support future strategies to strengthen school-based reproductive health education, teacher capacity, and cross-sector collaboration.